Faktor Penentu Surplus Underwriting Dana Tabarru’ Asuransi Jiwa Syariah di Indonesia Periode 2015-2020 - Emy Widyastuti; Anis Sholihah (el-Jizya: Jurnal Ekonomi Islam, 2022)
The occurrence of a high underwriting surplus will greatly benefit the company and have an impact on the level of public confidence in the services and products offered by sharia insurance so that people will choose the company as a place to do insurance. This requires the underwriter to carry out underwriting management properly so that there is an underwriting surplus. This study was conducted to determine the effect of premiums, claims and investment returns on the underwriting surplus of tabarru' funds for full sharia life insurance in Indonesia in 2015-2020. This research method is done through panel data regression. Research data in the form of secondary data with purposive sampling as a technique used in the research sample. Partially, the results show that premiums have a significant positive effect on the underwriting surplus, claims have a significant negative effect on the underwriting surplus, and investment returns have an insignificant negative effect on the underwriting surplus. Simultaneous testing shows that premiums, claims and investment returns have a significant effect on the underwriting surplus.